2011
DOI: 10.1590/s1415-47572011005000034
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of xenobiotic metabolizing genes (CYP1A1 and GSTP1) in sporadic head and neck cancer patients

Abstract: CYP1A1 is the phase I enzyme that detoxifies the carcinogen or converts it into a more electrophilic form, metabolized by phase II enzymes like GSTP1. These detoxifying genes have been extensively studied in association with head and neck cancer (HNC) in different ethnic groups worldwide. The current study was aimed at screening genetic polymorphisms of genes CYP1A1 and GSTP1 in 388 Pakistani HNC patients and 150 cancer-free healthy controls, using PCR-SSCP. No already known variants of either gene were found,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 26 publications
(36 reference statements)
1
3
1
Order By: Relevance
“…In current study statistically significant downregulation of GSTP1 was observed in brain tumor samples compared to control samples. Similar results have also been observed in breast cancer (Erlap et al, 2013), prostate cancer (Okino et al, 2007;Re et al, 2011) and colon cancer (Ritchie et al, 2009).Whereas conflicting results for GSTP1 expression pattern have been reported in some of other studies (Masood et al, 2011;Uchida et al, 2013). In present study, significant down-regulation of GSTP1 was observed in more advance grade of brain tumor samples when compared with early grade of brain tumor.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In current study statistically significant downregulation of GSTP1 was observed in brain tumor samples compared to control samples. Similar results have also been observed in breast cancer (Erlap et al, 2013), prostate cancer (Okino et al, 2007;Re et al, 2011) and colon cancer (Ritchie et al, 2009).Whereas conflicting results for GSTP1 expression pattern have been reported in some of other studies (Masood et al, 2011;Uchida et al, 2013). In present study, significant down-regulation of GSTP1 was observed in more advance grade of brain tumor samples when compared with early grade of brain tumor.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results have also been observed in lung cancer and human endothelial cell (Shah et al, 2009;Conway et al, 2009). Whereas conflicting results for CYP1A1 expression pattern have been reported in some of other studies in different cancers (Chang et al, 2007;Masood et al, 2011;Hafeez et al, 2012). Significant upregulation of CYP1A1 was observed in different types of brain tumors in current study.…”
Section: Discussioncontrasting
confidence: 84%
“…Upper aerodigestive tract malignancies constitute 4-5% of all malignancies. It is the sixth most common cancer worldwide and constitutes a significant global problem with half of a million new cases diagnosed every year resulting in an average mortality rate of 7.3 and 3.2 per 100,000 males and females respectively [ 3 ]. In South East Asia, it is the second most common cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with pharyngeal and laryngeal cancer, 42 head and neck cancer 43 two intronic deletions in the non‐coding regions of human GSTP1 were found – C1074 in intron 3 and C1466 in intron 4 that may result in differential binding of putative regulatory proteins. Lo and Ali‐Osman 44 identified a p53‐binding motif in intron 4 of human GSTP1 by which a wild‐type p53 regulates expression of gene and this could lead to protection against genotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with pharyngeal and laryngeal cancer, 42 head and neck cancer 43 Lo and Ali-Osman 41,45 demonstrated that in intron 5 of human GSTP1 contains retinoic acid response elements that are responsible for induction of gene expression. We found 6 SNPs, 1 deletion and 1 insertion in this canine GSTP1 intron.…”
Section: Discussionmentioning
confidence: 99%